British-French exchanges in the eighteenth century - Doig, Kathleen Hardesty, 1946-; Medlin, Dorothy, 1931-2011 (Cambridge Scholars Publishing, 2007)
France and Great Britain, so close geographically but separated by language, culture and history, had been exchanging merchandise, visitors, rulers and ideas for hundreds of years before the eighteenth century. The flow of traffic only quickened during this period, and became a flood, in the direction of Great Britain, during the decade following the Revolution. While certain of these exchanges, such as Voltaire's sojourn abroad, have been studied in detail, others are coming into focus only ...